2017
DOI: 10.1080/10454446.2017.1378143
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions toward sugar content of fruit juice products in a developing country

Abstract: The purpose of this paper is to determine consumer perceptions toward sugar content of fruit juice (FJ) products in South Africa amid the current sugar tax debate. The paper also ascertains how and if consumption patterns and socio-demographic factors are associated with consumer perceptions toward FJ sugar content. A cross-sectional study was conducted via structured self-administered questionnaires, which were disseminated on a face-to-face basis. Over 7600 consumers aged 16-66+ years in suburbs, townships, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Participants reported that packaged foods, particularly soft drinks, contain high amounts of sugars. In a study in South Africa, consumers considered fruit-based soft drinks to be high in sugar but frequently consumed these products, mainly because of low prices, marketing strategies, and personal preferences ( 27 ). Participants also mentioned interest in reducing sugar intake, particularly from homemade foods.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported that packaged foods, particularly soft drinks, contain high amounts of sugars. In a study in South Africa, consumers considered fruit-based soft drinks to be high in sugar but frequently consumed these products, mainly because of low prices, marketing strategies, and personal preferences ( 27 ). Participants also mentioned interest in reducing sugar intake, particularly from homemade foods.…”
Section: Discussionmentioning
confidence: 99%